Genetic analysis for seven pea varieties and their half diallel hybrids for forage and seed yield - Tawfiq, Sh Ismael; Abdulla, S Muhammad Sheikh (Sulaimani Journal for Pure and Applied Sciences, 2014)
The present experiment was conducted at the experimental farm of Qlyasan research Station- College of Agriculture during two growing seasons from November 2008 to may 2010 in a Randomized Complete Block Design (RCBD) with three replications, to study some genetic parameters in seven pea varieties (Avolla, America, Jeza, Joneor, Pack land, Wild local arvena and Samara) using half diallel crossing system. The highest value for number of root nodules/plant, weight of root nodules/plant produced by the hybrid Joneor× Wild local arvena. The desirable high negative heterosis value for the character number of days to 50% flowering and maturity recorded by the hybrid Jeza× Wild local arvena as the result of reducing the values of these characters in this hybrid comparing to its parental values. Regarding the general combining ability effect, the parents America, Jeza and Pack land were the best general combiner in reducing number of days to flowering and maturity. Parent Joneor was found to be the best general combiner for most studied characters such as plant height, plant dry weight, number of root nodules/plant, weight of root nodules/plant.The hybrids Jeza× Wild local arvena and Avolla× Samara recorded maximum negative value for the characters number of days to 50% flowering and physiological maturity respectively. Maximum positive value of this effect for the characters plant height and weight of root nodules/plant exhibited by the hybrid Avolla× Joneor, while the hybrid Jeza× Wild local arvena showed maximum effect for the characters number of basal branches/plant, root dry weight/plant. The variance components due to sca was larger than that of gca for most studied character except number of days to 50% flowering, recording the ratio of σ2gca/σ2sca to be more than one in these characters.The average degree of dominance was more than one in most studied characters, confirming the importance of non additive gene effect in the inheritance of these characters. Heritability in broad sense was found to be high in most studied characters. Heritability in narrow sense was high for the characters number of days to 50% flowering, physiological maturity, while it was moderate for the characters plant height, number of basal branches/plant, plant dry weight, leaf/stem ratio, dry weight root/plant, number of root nodules/plant, weight of root nodules/plant.
Keywords: Pea; gca; sca; Heterosis